2020
DOI: 10.48550/arxiv.2007.07058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ultraviolet sensitivity of the cosmological sequester

Michaela G. Lawrence,
David Seery

Abstract: We revisit the "sequester" proposal of Kaloper, Padilla and collaborators, in which the amplitude of the cosmological constant is decoupled from large contributions due to loops containing Standard Model particles. We review the different formulations of the model that have appeared in the literature, and estimate the importance of a particular class of quantum corrections-those that dress the interaction between the "rigid" scalars and infrared properties of the spacetime such as its 4-volume and integrated c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(77 reference statements)
0
4
0
Order By: Relevance
“…In particular, 1PI matter and graviton loops modify the cosmological constant, while pure gravity loops are responsible for the corrections to the gravitational coupling. An exhaustive analysis of the different effects of the quantum corrections and the ultraviolet sensitivity of sequestering, both in the Jordan and Einstein frames, is presented in reference [58]. In the case of the sequestering model, it has been shown that to cope with graviton loops the local model must be extended [59].…”
Section: Graviton Loopsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, 1PI matter and graviton loops modify the cosmological constant, while pure gravity loops are responsible for the corrections to the gravitational coupling. An exhaustive analysis of the different effects of the quantum corrections and the ultraviolet sensitivity of sequestering, both in the Jordan and Einstein frames, is presented in reference [58]. In the case of the sequestering model, it has been shown that to cope with graviton loops the local model must be extended [59].…”
Section: Graviton Loopsmentioning
confidence: 99%
“…This yields a constraint that is a polynomial in the difference Λ − T /4. Moreover, when the variational constraint is not explicitly dependent on M 2 P , all of the Planck mass dependent contributions cancel from the residual energy-momentum tensor, at least to leading order [58,59].…”
Section: The Gauss-bonnet Invariantmentioning
confidence: 99%
“…An exhaustive analysis of the different effects of the quantum corrections and the ul-traviolet sensitivity of sequestering, both in the Jordan and Einstein frames, is presented in Ref. [56]. In the case of the sequestering model, it has been shown that to cope with graviton loops the local model must be extended [57].…”
Section: Graviton Loopsmentioning
confidence: 99%
“…This yields a constraint that is a polynomial in the difference Λ − T /4. Moreover, when the variational constraint is not explicitly dependent on M 2 P , all of the Planck mass dependent contributions cancel from the residual energy-momentum tensor, at least to leading order [56,57].…”
Section: A the Gauss-bonnet Invariantmentioning
confidence: 99%